2009
DOI: 10.1016/j.bbr.2009.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential actions of adenosine A1 and A2A antagonists on the effort-related effects of dopamine D2 antagonism

Abstract: Adenosine and dopamine receptors in striatal areas interact to regulate a number of different functions, including aspects of motor control and motivation. Recent studies indicate that adenosine A 2A receptor antagonists can reverse the effects of dopamine (DA) D 2 antagonists on instrumental tasks that provide measures of effort-related choice behavior. The present experiments compared the ability of the adenosine A 2A antagonist KW6002, the nonselective adenosine antagonist caffeine, and the adenosine A 1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 78 publications
9
69
0
Order By: Relevance
“…Though previous work has shown that MSX-3 had no effect of FR5/chow feeding choice performance when administered on its own (Farrar et al 2007), co-administration of MSX-3 significantly reversed the behavioral effects of IL-1β injections, restoring the baseline behavioral pattern by increasing lever pressing and decreasing chow intake in IL-1β-treated rats. These results are consistent with previous research demonstrating that adenosine A 2A receptor blockade or genetic deletion can reverse the effort-related effects of DA antagonism and depletion (Farrar et al 2007, 2010; Worden et al 2009; Mott et al 2009; Salamone et al 2009; Nunes et al 2010; Pardo et al 2012). Furthermore, the present findings are consistent with reports showing that the adenosine A 2A antagonists can produce effects that are consistent with the behavioral profile of an antidepressant in rodents tested on the swim test or tail suspension task (El Yacoubi et al 2001; Hodgson et al 2009; Hanff et al 2010).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Though previous work has shown that MSX-3 had no effect of FR5/chow feeding choice performance when administered on its own (Farrar et al 2007), co-administration of MSX-3 significantly reversed the behavioral effects of IL-1β injections, restoring the baseline behavioral pattern by increasing lever pressing and decreasing chow intake in IL-1β-treated rats. These results are consistent with previous research demonstrating that adenosine A 2A receptor blockade or genetic deletion can reverse the effort-related effects of DA antagonism and depletion (Farrar et al 2007, 2010; Worden et al 2009; Mott et al 2009; Salamone et al 2009; Nunes et al 2010; Pardo et al 2012). Furthermore, the present findings are consistent with reports showing that the adenosine A 2A antagonists can produce effects that are consistent with the behavioral profile of an antidepressant in rodents tested on the swim test or tail suspension task (El Yacoubi et al 2001; Hodgson et al 2009; Hanff et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, reductions in the presence of the DA metabolite homovanillic acid in cerebrospinal fluid were correlated with the degree of fatigue in patients treated with IFN-α (Felger and Miller 2012). These results suggest that cytokines may exert effects on DA that cause animals to reallocate their instrumental response selection based upon the response requirements of the task, and select lower cost alternatives to obtain food (Salamone et al 2007, 2009). Furthermore, as described above, the effects of IL-1β in rats responding on the FR5/chow feeding choice procedure resembled those produced by DA antagonism or depletion (Salamone et al 2007; Salamone and Correa 2012).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…adults), wide dosage range, or flexible dose protocols are yet to be conducted. Interestingly, caffeine improves cognitive performance in an animal model of ADHD [121] and promotes effortrelated behavior in animals treated with dopamine antagonists [122]. Therefore, based on observational and experimental studies, caffeine is a candidate treatment for ADHD.…”
Section: Dr Lara / Caffeine and Psychiatrymentioning
confidence: 99%